Feeding of children that living with aids: family/care guivers experiences in group activity - Stela Maris de Mello Padoin; Cristiane Cardoso de Paula; Izabel Cristina Hoffmann; Maria Clara Valadão; Andressa Peripolli Rodrigues; Tassiane Ferreira Langendorf (Universidade Federal de Santa Maria, 2012)
Objective: the objective is to describe the experience in a group with family members of children who living with acquired immunodeficiency syndrome, highlighting the theme of child feeding. Method: experience report on the care provided to children and their families / care givers in a teaching hospital. Results: the group Guardian Angels is characterized by dynamic and interactive way that the participants present their experiences, needs and concerns of the child's clinical condition and their social integration, mediated dialogue. Among the main issues, infant feeding stands out as one of the greatest difficulties faced in the families. Conclusions: group activities in health education reinforce the need to deconstruct the traditional care model for a care that is centered on the family members' needs and child development through the continuity of a multi-professional care staff